Business history of hospitals in the 20th century : entrepreneurship, organization, and finances - Fernández Pérez, Paloma 1964- (Colección de libros electrónicos de ULoyola, 2024)
This book offers a business history of modern hospitals in the 20th century. Presenting case studies from around the world, it examines the long-term institutional and historical evolution of hospital organization and management models, applying a business history approach to do so. Drawing on reports from international organizations and other historical data, it explores the evolution, path dependencies, actors and institutions that have shaped the diversity of hospital organization and management models. At the same time, it analyzes the historical origins of major problems faced by todays hospitals, such as cost-inefficiencies, lack of specialized human capital, etc. The contributing authors cover topics such as the history of hospital finance and accounting, hospital price regulation, entrepreneurship models, hospital privatization, and hospital governance. The book will appeal to scholars and students of economic and business history, and to anyone interested in the history of hospitals.